TEM and STEM analysis on heat-treated and in vitro plasma-sprayed hydroxyapatite/Ti-6Al-4V composite coatings - Dong, Zhili (2012)
A cogent understanding of the microstructure, and indeed nano-structure, of hydroxyapatite (HA) and the interface between Ti-6Al-4V and HA is crucial to its appropriateness as a biomaterials. This paper reports the analysis of plasma-sprayed HA/Ti-6Al-4V composites by transmission electron microscopy (TEM) and scanning transmission electron microscopy (STEM) to elucidate the intricate nature of the materials following plasma spray processing and in vitro evaluation. The novel Ti-6Al-4V/HA composite coating, with approximately 48 wt% HA, had demonstrated attractive tensile adhesion strength (~28 MPa) and improved Young’s modulus (~ 55 GPa). Experimental results demonstrated that amorphous calcium phosphate and fine HA grains were formed during rapid splat solidification in the as-sprayed composite coatings. Small Ti-6Al-4V grains were observed adjacent to the amorphous calcium phosphate. The coatings were further heat treated at 600°C for 6 h, and significant crystallisation of the amorphous calcium phosphate phase took place. However, complete crystallisation was not achieved at this temperature, as the coatings invariably contained a small amount of amorphous calcium phosphate phase in some local regions. After immersion in simulated body fluid for 2 weeks and 10 weeks, TEM and STEM confirmed that the interfaces inside the coating maintained good microstructural integrity.